Photocorrosion Mechanism of TiO2-Coated Photoanodes - Arjen Didden; Philipp Hillebrand; Bernard Dam; Roel van de Krol (International Journal of Photoenergy)
Atomic layer deposition was used to coat CdS photoanodes with 7 nm thick TiO2 films to protect them from photocorrosion during photoelectrochemical water splitting. Photoelectrochemical measurements indicate that the TiO2 coating does not provide full protection against photocorrosion. The degradation of the film initiates from small pinholes and shows oscillatory behavior that can be explained by an Avrami-type model for photocorrosion that is halfway between 2D and 3D etching. XPS analysis of corroded films indicates that a thin layer of CdS remains present on the surface of the corroded photoanode that is more resilient towards photocorrosion.